Accounting for preferences and beliefs in social framing effects - Bernold, Elizabeth; Gsottbauer, Elisabeth; Ackermann, Kurt A.; Murphy, Ryan O. (Frontiers in Behavioral Economics, 2023)
Past experiments show systematic differences in contributions to public goods under various framing conditions. Several explanations of these differences have been presented. Some suggest that social frames affect subjects' preferences, while others suggest that framing changes subjects' beliefs about others, and thus in turn affects behavior. In this paper, we test the effect of framing on the level of contributions in a series of public goods games designed to separate the impact of preferences from beliefs in shaping cooperative decisions. This is achieved by implementing a social value orientation measure to elicit social preferences from decision makers, which are then analyzed in concert with reported beliefs about others’ cooperation and own contribution decisions from the linear public goods games. While we find mixed results on framing effects, our study demonstrates that preferences and beliefs are significant predictors of cooperation. Furthermore, the degree to which they influence cooperation is either strengthened or weakened by framing.